1997
DOI: 10.1177/0730888497024004005
|View full text |Cite
|
Sign up to set email alerts
|

Do the Determinants of Promotion Differ for Blacks and Whites?

Abstract: A central assumption of much of the previous research on race differences is that the process by which Blacks and Whites advance in the workplace is race blind so that if Blacks and Whites had the same amount of education and job experience and were located across the same bureaucratized structures, the gap in Black-White attainment in the workplace would disappear. The authors argue that to understand the systematic differences in Black-White outcomes in the workplace, we need to reexamine this assumption. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 41 publications
3
127
0
Order By: Relevance
“…A representative sample of U.S. workers revealed a negative association between the proportions of Black employees in the organization and promotion rates for Blacks, but no parallel association for Whites (Baldi and McBrier 1997). The overrepresentation of Whites in managerial positions may help explain why negative career outcomes accrue to Blacks but not Whites in the presence of higher proportions of same-race peers.…”
Section: Demographic Match and Promotionsmentioning
confidence: 99%
“…A representative sample of U.S. workers revealed a negative association between the proportions of Black employees in the organization and promotion rates for Blacks, but no parallel association for Whites (Baldi and McBrier 1997). The overrepresentation of Whites in managerial positions may help explain why negative career outcomes accrue to Blacks but not Whites in the presence of higher proportions of same-race peers.…”
Section: Demographic Match and Promotionsmentioning
confidence: 99%
“…A firm with one job obviates any additional segregating effects of the matching process. Similarly, the well-documented segregating effects of promotions and internal job ladders (Baldi and McBrier, 1997;Diprete and Soule, 1988;Doeringer and Piore, 1971;James, 2000;Kelley, 1982;Maume, 2004;Miech, Eaton and Liang, 2003;Smith, 2005;Thomas and Gabarro, 1999;Wilson, Sakura-Lemessy and West, 1999) are controlled for by using a one-job firm. Second, to control for human capital and other individual-characteristics explanations for disparate labor market outcomes, all agents in the model are defined as being identically qualified for the job and performing equally well while on the job.…”
Section: Model Definitionmentioning
confidence: 99%
“…Similarly, Giscombe and Mattis (2002) found women of color "less optimistic" than White women about future advancement. Baldi and McBrier (1997) have suggested that the subjectivity often inherent in the promotion process permits discrimination to occur in subtle, difficult-toidentify ways.…”
mentioning
confidence: 98%